Fumigant toxicity and sublethal effects of Thymus munbyanus essential oil on biomarkers, reproduction, and locomotion in the Mediterranean flour moth Ephestia kuehniella - Hamida, Zahia C.; Bendjedid, Hadjira; Oulhaci, Mohamed C.; Yezli, Amina; Yezli-Touiker, Samira (Archives of Biological Sciences, 2026)
Paper description: Thymus munbyanus essential oil was evaluated as a botanical fumigant for controlling the Mediterranean flour moth, Ephestia kuehniella, a major pest of stored grain products. A range of fumigation concentrations was first tested to determine the lethal doses causing 25% and 50% mortality, which were then used to assess sublethal effects on adult survival and behaviour. Exposure induced oxidative stress responses by increasing glutathione S-transferase and catalase activities, and caused neurotoxicity through acetylcholinesterase inhibition. Reduced mobility and reproductive performance suggest long-term population suppression potential, supporting the development of eco-friendly botanical insecticides. Abstract: This study evaluated the fumigant toxicity of Thymus munbyanus subsp. coloratus essential oil against adult Ephestia kuehniella (Zeller). To determine sublethal effects, we integrated biochemical biomarkers with assessments of reproductive performance and locomotor activity. Adults were exposed via fumigation to concentrations between 0.05 and 0.8 μL/mL of air, with lethal concentrations calculated after 24 h of exposure. The essential oil showed strong fumigant activity, with LD25 and LD50 values of 0.153 and 0.26 μL/mL of air, respectively. Sublethal exposure at these concentrations was associated with changes in biomarker responses in adults, including increased glutathione S-transferase (GST) and catalase (CAT) activities, along with decreased acetylcholinesterase (AChE) activity. In addition, fumigation affected adult reproductive performance by reducing oviposition, as reflected by a decrease in the number of eggs laid and hatched. Locomotor activity was also impaired, with reductions in distance traveled, movement duration, and movement speed. Overall, these findings suggest that T. munbyanus essential oil has potential as a botanical fumigant against E. kuehniella adults.